Nurse and pregnancy - ES Hajikazemi (Iran University of Medical Sciences, 1994)
EXTRACT: Although all pregnant women are worry about their fetus, it is more serious in pregnant nurses. We are not talking about Hydatidform mole, Amniotic fluid embolism, and Sheehans syndrome. Fortunately these disorders are rare. Instead what are serious for a pregnant nurse are infection diseases, radioactive materials, anticancer agents, and other chemicals. Meanwhile when a nurse remove patient in bed or give a good shape to a bed, it's possible to be hurt. In order to protect herself and her fetus from any damage, she should consult to an obstetrician about her job's details immediately, and be aware of securities in her job's environment.